Micro- and Nanoscale Pore Structure Characterization and Mineral Composition Analysis of Clayey-Silt Hydrate Reservoir in South China Sea - Cheng Lu; Yuxuan Xia; Xuwen Qin; Chao Ma; Hang Bian; Donghui Xing; Hongfeng Lu (Geofluids)
Natural gas hydrate is a kind of environmentally friendly unconventional energy with large reserves, which attract increasing attention in recent years. The microscopic pore structure and mineral composition of natural gas hydrate reservoir have a great influence on its seepage characteristics during exploitation. In this study, computed tomography and scanning electron microscope are used to obtain digital images of three clayey-silt natural gas hydrate reservoir samples in the Shenhu area of South China Sea, and then, the pore structure and the mineral composition of the samples are obtained after image processing. The result indicates that the clayey-silt samples show strong hydrophilic characteristics, small particles, good sorting properties, variable pore distribution, small average pore and throat radius, large porosity, and a large content of submicron pores. The mineral composition of the reservoir is mainly quartz and contains a certain amount of clay minerals, mainly illite, while the mineral composition of reservoir rich in microbial fossils is mainly carbonate. The results indicate that the pore structure and mineral composition of natural gas hydrate reservoirs in Shenhu area lay a foundation for the efficient development of the clayey-silt reservoir.